Risk Factors and Outcomes in Cats with Acquired Myasthenia Gravis (2001–2012). (26th August 2015) - Hague, D.W.; Humphries, H.D.; Mitchell, M.A.; Shelton, G.D.
<x xml:space="preserve">Abstract</x> Background Acquired myasthenia gravis (MG) in cats most commonly causes generalized weakness without megaesophagus and is more often associated with a cranial mediastinal mass, compared to dogs. Hypothesis/Objectives To extend the clinical findings described in the report of 2000 on MG in cats (J Am Vet Med Assoc 215:55–57). Animals Two hundred and thirty‐five cats with MG. Methods Retrospective case study to evaluate the long‐term outcome and incidence of spontaneous remission in myasthenic cats. Information including signalment, clinical presentation, presence of and type of cranial mediastinal mass, treatment including surgical versus medical, survival time, and outcome including spontaneous remissions was collected and analyzed in cats diagnosed at the Comparative Neuromuscular Laboratory, University of California San Diego by detection of acetylcholine receptor antibody titers >0.3 nmol/L by immunoprecipitation radioimmunosassay. Results Acquired MG in cats is associated with a euthanasia rate of 58%. Abyssinian and Somali cats had an increased incidence of MG compared to mixed breed cats or cats of other breeds. A cranial mediastinal mass, most commonly thymoma, was observed in 52% of the cats, which is higher than in the previous report. Spontaneous remission is not a characteristic of MG in cats. Conclusions and clinical importance Myasthenia gravis in cats is a chronic disease associated with a high incidence of a cranial mediastinal mass. Spontaneous remission is not common and clinicians should warn owners of the necessity for long‐term treatment. The clinical outcome with a cranial mediastinal mass did not differ between surgical or medical treatment.